Nuclear and particle physics aspects of Big Bang nucleo-synthesis - Civitarese, Enrique Osvaldo (2011)
Big Bang Nucleo Synthesis (BBN) is the process which has occurred during the first three minutes of the Universe, that is during the time it needed to cooled down to temperatures of the order of 109 K. The standard BBN model depends on one parameter, the baryonic density, and it is one of the proper tools to study the physics of the Universe at its earliest stage. In this paper we shall discuss the rol of BBN as a testing ground for evidences and possible limits which could be determined from cosmological analysis based on the inclusion of sterile neutrinos, the variation of the mass of the Higgs boson and the time variation of fundamental constant.